2020
DOI: 10.1371/journal.pone.0232522
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of biochemical profile of Chronic Kidney Disease of uncertain etiology in Sri Lanka

Abstract: Chronic Kidney Disease of uncertain etiology (CKDu) is an endemic, disease that mostly affects young agricultural workers in the rural dry zone of Sri Lanka. This study was designed to identify specific biochemical manifestations of CKDu cases. All (119) nondialysis definite CKDu patients in Girandurukotte and Wilgamuwa were selected. Blood and urine samples were collected and measured biochemical parameters. All analyses were performed in IBM SPSS statistics version 23 (IBM Corp, USA). The median blood pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
(44 reference statements)
4
1
2
Order By: Relevance
“…The strong positive correlations between the serum levels of AST and ALT with eGFR in the current study indicate that as the severity of CKD increases, the mean values of aminotransferases significantly decreased. These results are in agreement with a number previous studies [ 12 , 13 , 28 ]. Thus, hepatic aminotransferases follow a specific pattern at different stages of CKD and are used as indicators of the progression of CKD.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The strong positive correlations between the serum levels of AST and ALT with eGFR in the current study indicate that as the severity of CKD increases, the mean values of aminotransferases significantly decreased. These results are in agreement with a number previous studies [ 12 , 13 , 28 ]. Thus, hepatic aminotransferases follow a specific pattern at different stages of CKD and are used as indicators of the progression of CKD.…”
Section: Discussionsupporting
confidence: 94%
“…On the contrary, the present study showed that there was no significant difference in the serum levels of both total and direct bilirubin across the clinical stages of CKD, which agrees with previous studies [ 13 , 28 ]. In contrast to our findings, a study conducted in Iraq showed that the mean serum level of total bilirubin was significantly decreased in CKD patients under dialysis when compared with their mean levels in CKD patients not undergoing dialysis.…”
Section: Discussionsupporting
confidence: 93%
“…In most community studies, declined renal function in the absence of diabetes mellitus, hypertension, and glomerular diseases is treated as CKDu or CKD of nontraditional causes. These clinical manifestations associated with CKDu were confirmed in a recent study with CKDu patients in Sri Lanka [ 25 ]. Nonetheless, several community studies conducted in 2019 in CKDu affected regions indicate the gravity of this epidemic.…”
Section: Chronic Kidney Disease Of Unknown Etiology (Ckdu)supporting
confidence: 61%
“…By way of comparison, among a population of 377 Mexican American and Other Hispanic American males aged 18-40 reported by the U.S. National Health and Nutrition Examination Survey (NHANES) from 2017 March 2020, the mean value of HbA1c was 5.42% (SD: 0.80) and the prevalence of elevated HbA1c was 13.5% (compared to 21% in our cohort), while the average BMI was 29.37 kg/m 2 (SD: 6.46) compared to 21.7 kg/m 2 in our cohort [46]. One other study in the CKDu literature that has reported levels of HbA1c was recently published from Sri Lanka, which found nearly 60% of participants with elevated HbA1c, and another 16% in the diabetic range [47]. Raines and colleagues reported 3.7% of participants in the diabetic range among cases in a study in Nicaragua, however that paper did not report results for the prediabetic range, limiting our ability to draw comparisons [48].…”
Section: Nutritional Markers Underlying Health and Kidney Functioncontrasting
confidence: 44%